ECONOMICS OF PIG REARING UNDER TRADITIONAL SYSTEM IN ARUNACHAL PRADESH* (Indian Journal of Animal Production and Management, 2014)
The study was conducted in East Siang district of Arunachal Pradesh to know the economics of pig rearing in various systems of management. One hundred pig farmers having minimum of two pigs each which were selected from five blocks within the district. The result revealed that 70% of the farmers were agri-farmer and animal raiser. 75% of the farmers fed there pigs twice a day. All the farmers reared pig because there were no any religious taboos. All the farmers used family labours to look after the pigs. Average annual family income from piggery, other source and total income were found to be Rs. 19085.00±0.62, 85059.00±6.24 and 105044.00±6.15 respectively. 65.00% of pigs were reared in scavenging system and net return per pig was highest in scavenging system of rearing (Rs.12056.9).
Keywords: Economics; agri-farmers; pigsty; piggery; scavenging system